Aluminum and Cadmium Forms in Stressed Rhizosphere Soil and Their Bioavailability to Two Hordeum vulgare L. Varieties. Issue 4 (30th August 2013) - Guo, Tian‐Rong; Sun, Lifu; Han, Li; Qiu, Muqing
<x xml:space="preserve">Abstract</x> The effects of aluminum (Al) and cadmium (Cd) single and combinational treatments on two barley varieties differing in Al tolerance were examined in terms of chemical forms of Al and Cd in the rhizosphere soil and their plant availability. Our results showed that acidic‐soluble inorganic Al, humic acidic Al, and residue Cd were the predominant form(s) of Al and Cd in the rhizosphere soil of both barley varieties. The contents of different Al and Cd forms, especially for the exchangeable form, as well as Al and Cd contents in plants significantly increased under stress treatments. Meanwhile, stress treatments significantly reduced grain yield. In comparison with the single metal treatments, combinational stress increased the contents of exchangeable Al and Fe–Mn‐oxide‐bound Cd, but showed a decrease or no effect on the other forms. As a result, combinational stress led to a higher Al but a lower Cd accumulation in plants, and more reduction in grain yield. Increase in the contents of bioavailable Al and Cd forms in the stressed rhizosphere soil and in the concentrations of Al or Cd in plant parts was higher in the Al sensitive variety.